Final answer:
The expressions 2(x+3) and 2x+4+2x are not equivalent.
Step-by-step explanation:
To determine if the expressions 2(x+3) and 2x+4+2x are equivalent, we can simplify them and compare the results. Let's simplify each expression when x=1:
2(x+3) = 2(1+3) = 2(4) = 8
2x+4+2x = 2(1)+4+2(1) = 2+4+2 = 8
Both expressions evaluate to 8 when x=1, so they are equivalent. Now, let's evaluate the first expression when x=2:
2(x+3) = 2(2+3) = 2(5) = 10
The first expression evaluates to 10 when x=2, which is different from the value of 8 obtained from the second expression. Therefore, the expressions 2(x+3) and 2x+4+2x are not equivalent.